PELAKSANAAN STANDARD OPERATIONAL PROCEDURE MAKE-UP ROOM DI MUTIARA MERDEKA HOTEL PEKANBARU - Silvia Okta Dumyati; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The hospitality business is growing and developing very well in Indonesia, especially in big cities. The purpose of the writing is to find out the implementation of the standard operational procedure make-up room in the housekeeping department at Mutiara Merdeka Hotel Pekanbaru. In writing this final project report, the author uses a writing method data collection techniques by means of interviews and literature studies with qualitative descriptive techniques. The results of this study can be concluded that the implementation of the Standard Operational Procedure (SOP) has been running well at Mutiara Merdeka Hotel Pekanbaru. Roomboys are also required to create guest satisfaction and comfort from the services provided to minimize and prevent guest complaints. Keywords: SOP, Make-up Room